2009
DOI: 10.1073/pnas.0906785106
|View full text |Cite
|
Sign up to set email alerts
|

A transcription co-factor integrates cell adhesion and motility with the p53 response

Abstract: Despite its obvious importance in tumorigenesis, little information is available on the mechanisms that integrate cell motility and adhesion with nuclear events. JMY is a transcription co-factor that regulates the p53 response. In addition, JMY contains a series of WH2 domains that facilitate in vitro actin nucleation. We show here that the ability of JMY to influence cell motility is dependent, in part, on its control of cadherin expression as well as the WH2 domains. In DNA damage conditions JMY undergoes nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
165
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(173 citation statements)
references
References 49 publications
7
165
1
Order By: Relevance
“…One interesting example is JMY (junction-mediating and regulatory protein), a cytoplasmic actin-binding protein that can promote microfilament polymerization and directly interacts with p53 and p300/CBP. [84][85][86][87] After DNA damage, JMY accumulates in the nucleus, in which it associates with p53 and the tetratricopeptide repeat-containing protein STRAP to form a complex that includes p300/CBP, and promotes p53-dependent transcription and apoptosis. 84,87 Interestingly, STRAP can also recruit within this complex the arginine methylase PRMT5 that modifies three residues in the C-terminal region of p53.…”
Section: And References Therein)mentioning
confidence: 99%
“…One interesting example is JMY (junction-mediating and regulatory protein), a cytoplasmic actin-binding protein that can promote microfilament polymerization and directly interacts with p53 and p300/CBP. [84][85][86][87] After DNA damage, JMY accumulates in the nucleus, in which it associates with p53 and the tetratricopeptide repeat-containing protein STRAP to form a complex that includes p300/CBP, and promotes p53-dependent transcription and apoptosis. 84,87 Interestingly, STRAP can also recruit within this complex the arginine methylase PRMT5 that modifies three residues in the C-terminal region of p53.…”
Section: And References Therein)mentioning
confidence: 99%
“…Upon DNA damage, it was observed that JMY interacts with and forms a complex with p300 and Strap while recruiting PRMT5 into a co-activator complex that triggers p53 response [10]. According to Coutts et.al JMY's functional role in p53 response is evident in its associated increase with p53-dependent transcription induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…JMY localizes both in nucleus and cytoplasm [11], but following stress or DNA damage JMY starts to migrate from the cytoplasm to accumulate in the nucleus [10]. Metastasis is facilitated by increased cell motility, allowing tumour cells to invade and colonize surrounding as well as distant tissues.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations